The Evaluation of Narada Cup School Sport Program Using CIPP Evaluation Model - Rudy Pramono; Sarliyani Sarliyani; Agus Purwanto (Universitas Pendidikan Indonesia, 2020)
Narada Cup is one of the superior programs of the Narada Senior High School Student Council aimed at facilitating the development of student interests and talents and as a promotional event for the school. Considering the two big goals to be achieved and the plan to organize the next Narada Cup program, a comprehensive program evaluation process is needed to understand, explore, and improve the process of organizing it. This qualitative evaluation study used the CIPP evaluation model (context, input, process, product) with purposive sampling. The data collection was conducted through interview sessions, FGD (focus group discussion), observation, and documentation studies. This research results: (1) Context evaluation shows that formulating the vision and mission of the program will clarify the projections of long-term program objectives; (2) Input evaluation shows that the procurement of the manuals of implementation containing SOP (standard operational procedure) is needed; (3) Process evaluation concludes that the recording of the problem-solving process was used as an evaluation reference for all parties, so that the future implementation of the program would be better; (4) Product evaluations conclude that Narada Cup program is recommended to be continued annually and continuously evaluated and refined for the development and improvement of the quality of this program. Abstrak Piala Narada adalah salah satu program unggulan OSIS SMA Narada yang bertujuan memfasilitasi pengembangan minat dan bakat siswa dan sebagai acara promosi untuk sekolah. Mempertimbangkan dua tujuan besar yang ingin dicapai dan rencana untuk menyelenggarakan program Piala Narada berikutnya, proses evaluasi program diperlukan secara komprehensif untuk memahami, mengeksplorasi, dan meningkatkan proses pengorganisasian itu. Studi evaluasi kualitatif studi kasus ini menggunakan model evaluasi CIPP (konteks, input, proses, produk) dengan pengambilan sampel purposive dan pengumpulan data dilakukan melalui sesi wawancara, FGD (diskusi kelompok fokus), observasi, dan studi dokumentasi. Hasil penelitian ini: (1) Evaluasi konteks menunjukkan bahwa merumuskan visi dan misi program akan memperjelas proyeksi tujuan program jangka panjang. (2) Evaluasi input, pengadaan manual implementasi yang berisi SOP (prosedur operasional standar). (3) Evaluasi proses menyimpulkan bahwa rekaman proses penyelesaian masalah digunakan sebagai referensi evaluasi dengan semua pihak sehingga implementasi program di masa depan akan lebih baik.  (4) Evaluasi produk menyimpulkan bahwa program Piala Narada direkomendasikan untuk dilanjutkan setiap tahun dan terus dievaluasi dan disempurnakan untuk pengembangan dan peningkatan kualitas program ini